2016
DOI: 10.18697/ajfand.74.13755
|View full text |Cite
|
Sign up to set email alerts
|

Morphological diversity of mango germplasm from the upper athi river region of eastern Kenya: An analysis based on non- fruit descriptors

Abstract: Phenotypic variation in plants can be evaluated by morphological characterization using visual attributes. Fruits have been the major descriptors for identification of different varieties of fruit crops. However, even in their absence, farmers, breeders and interested stakeholders require to distinguish between different mango varieties. This study aimed at determining diversity in mango germplasm from the Upper Athi River (UAR) and providing useful alternative descriptors for the identification of different m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
5
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 10 publications
7
5
0
2
Order By: Relevance
“…Similarly, Rymbai et al [41] studied eight mango cultivars from different agro-climatic areas in India and observed a monomorphism crown shape (semi-circular) for all the cultivars. These results are also in line with Toili et al [39] who evaluated 98 accessions from Kenya and showed that the crown shape of 70% of the germplasm was semi-circular with a growth habit predominantly spreading. However, Rajan et al [42] reported significant difference in canopy structure among 26 Indian mango cultivars.…”
Section: Variability In the Mango Germplasmsupporting
confidence: 90%
See 1 more Smart Citation
“…Similarly, Rymbai et al [41] studied eight mango cultivars from different agro-climatic areas in India and observed a monomorphism crown shape (semi-circular) for all the cultivars. These results are also in line with Toili et al [39] who evaluated 98 accessions from Kenya and showed that the crown shape of 70% of the germplasm was semi-circular with a growth habit predominantly spreading. However, Rajan et al [42] reported significant difference in canopy structure among 26 Indian mango cultivars.…”
Section: Variability In the Mango Germplasmsupporting
confidence: 90%
“…The present study revealed a relatively low genetic diversity for traits related to the tree crown, leaf, and inflorescence contrary to the fruit related traits showing higher diversity within the mango germplasm. This confirms the importance of fruit related traits as good differentiation variables of mango accessions [39]. Phenological data showed that this germplasm was predominantly of medium flowering and maturity types.…”
Section: Variability In the Mango Germplasmsupporting
confidence: 77%
“…This suggested the cultivars varied for all the quantitative traits that could be used for further breeding work. Similarly, authors from India (Singh et al, 2012;Bajpai et al, 2016) and Kenya (Toili et al, 2016;Gitahi et al, 2016) also reported the presence of significant differences among mango cultivars they studied considering similar quantitative traits.…”
Section: Variation Of Mango Cultivars In Quantitative Traitsmentioning
confidence: 79%
“…These characters are among the important attributes that could be utilized for classification of the cultivars (Sharma et al, 2016). Inline to this, Toili et al (2016), Krishnapillai and Wijeratnam (2016), Joshi et al (2013), Ribeiro et al (2013) and Raza et al (2017) report on mango cultivars in Kenya, Sri Lanka, Indian, Brazil and Pakistan, respectively showed significant variability with the aforementioned characters and suggested for **Significant at p<0.01, SE=standard error and CV (%) = coefficient of variation in percent. a Analysis of variance was not computed since the data were collected from a single tree.…”
Section: Tree and Leaf Charactersmentioning
confidence: 99%
See 1 more Smart Citation